Suddenly religious or irreligious: Mentawai converts vs local culture - Fitri, Aulia; Karni, Awis; Ashadi, Andri (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2025)
This research aims to find the phenomenon of Muslim life that is still carried out in daily life because of ancestral customs that are still inherent and thick in the Mentawai community. The research method used in this study is qualitative using a descriptive analysis approach. Data were collected using a semi-structured interview technique with open-ended questions. This technique is used to give the informant the freedom to answer according to their understanding, knowledge, and experience. The collected data was then analyzed using qualitative data analysis of the Miles and Huberman technique through three stages, namely data reduction, data exposure, and conclusion drawing and verification. This research found the patterns or thought events of Mentawai Muslims that are still influenced by ancestral culture. The results of the above study show that there is a cultural syncretism between Islamic teachings and local customs that form unique characteristics in the religious practices of the Mentawai people. This is reflected in the rituals, traditions, and social norms that are carried out, which at the same time strengthen the cultural identity as well as the faith of Muslims in the region. These findings make an important contribution to understanding the dynamics of the relationship between religion and culture in the context of indigenous peoples, as well as their implications for the preservation of cultural heritage